The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1038/sc.2013.151
|View full text |Cite
|
Sign up to set email alerts
|

Sexual function and associated factors in Iranian patients with chronic low back pain

Abstract: Study design: Case-control study. Objectives: (i) To describe the prevalence of sexual dysfunction in chronic low back pain (CLBP) patients, (ii) to compare the range of sexual function outcomes between patients with CLBP and healthy controls and (iii) to investigate which factors are associated with sexual function within the cohort of individuals with CLBP. Setting: Low back pain (LBP) clinic of Qazvin University of Medical Sciences, Qazvin, Iran. Methods: A total of 702 patients with CLBP and 888 healthy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
44
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 21 publications
7
44
1
1
Order By: Relevance
“…The higher levels of pain reported by patients with SD as compared to those who did not report SD in the present study may suggest that chronic pain could also be considered a risk factor for SD, as suggested by others [9][10][11][12][13][14][15][16]. This is strongly supported by the significant correlation between the VAS scores of pain intensity and severity of SD found in the present study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The higher levels of pain reported by patients with SD as compared to those who did not report SD in the present study may suggest that chronic pain could also be considered a risk factor for SD, as suggested by others [9][10][11][12][13][14][15][16]. This is strongly supported by the significant correlation between the VAS scores of pain intensity and severity of SD found in the present study.…”
Section: Discussionsupporting
confidence: 81%
“…More recently higher levels of SD were found in 166 women with chronic widespread pain compared to healthy women [13]. Another recent study on a large population of Iranian patients with chronic low back pain, showed a twice as high prevalence of SD compared to healthy controls (women 71.1% versus 36.8%; men 59.5% versus 24.5%, respectively) [14]. Higher prevalence of SD was also reported in male patients with migraine and tension type headaches [15] and in women with primary headaches [16].…”
Section: Introductionmentioning
confidence: 97%
“…Recently, a study was published about the association between low back pain and sexual dysfunction (SD) [9]. Not only physical constraints, but also emotional distress as well as other psychological factors have the potential to change the perception of sexuality in the spinal cord injured [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Although both the current study and the study of Brotto et al are based on fairly large sample sizes (269 and 132 women with PVD, respectively), women participating in the study of Brotto et al were all actively seeking treatment for their PVD symptoms, whereas the current study was based on a combined clinical and community sample, where participants may have been less distressed on average. Further, in the present study, duration of pain symptoms, age at first sexual intercourse attempt, and duration of the current partner relationship were controlled for because (i) they were different between the two groups yet are unrelated to etiology; and (ii) are either associated with sexual function and/or chronic pain outcomes [53,54].…”
Section: Discussionmentioning
confidence: 99%